IMPLEMENTASI KEBIJAKAN JAMINAN KESEHATAN DAERAH DI KABUPATEN PURBALINGGA PROVINSI JAWA TENGAH - Hari Walujo Sedjati (Jurnal Paradigma, 2020)
The research aimed to know problems policy health on Purbalingga district; province Central Java. Health planners have been more effective largely because of a policy regionalizing responsibility for the public health pure delivery assurance systems. Several kinds of health service provider’s hospital recommended by government for pure society in Purbalingga district. The Government as certain the efficiency and effectiveness of health services in public actors, these goals and options which frame a actor government Purbalingga district, choice in the health sector, are complicated by agreement over the criteria that determinant which patients are getting too much for pure society to health care. The policy Implementation goals to minimize mortalities and Invalid body for pure society in Purbalingga and policy health goals and standards are reached.